Anti-inflammatory and antioxidant potential of Syzygium polyanthum (Wight) Walp. bioactive compounds in polycystic ovary syndrome: An in silico study. - Renny Aditya; Budi Santoso; Widjiati Widjiati (GarVal Editorial Ltda., 2022)
Context: Polycystic ovary syndrome (PCOS) is significantly associated with inflammation and oxidative stress. Syzygium polyanthum is a plant rich in pharmacological properties. Aims: To evaluate the anti-inflammation and antioxidant potential of S. polyanthum bioactive compounds using in silico approach. Methods: The S. polyanthum was extracted using the ultrasound-assisted extraction (UAE) method, and the bioactive compounds were screened using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS) analysis. This study predicted the biological activity of S. polyanthum compounds using PASS Online server. Before docking, we analyzed the protein-protein interactions (PPIs) network of TNFα, NF-kB, SOD, and KEAP1. The molecular docking was done using Autodock Vina in PyRx software and visualized using Discovery Studio. Probability to be active (Pa) was determined. Results: The bioactive compounds found in S. polyanthum and used in this study were deoxyphomalone, NCGC00169066-01, and phloretin with retention times [min] of 0.886, 0.907, and 8.323, respectively. The predicted biological activity of compounds and controls were anti-inflammatory, immunosuppressant, TNF expression inhibitor, immunomodulatory and HIF1α expression inhibitor (Pa>0.5 for all S. polyanthum compounds and Pa<0.5 for SPD304, MG-132, and MDF). Based on PPIs network analysis, TNFα, NF-kB, SOD, and KEAP1 are associated. The molecular docking analysis showed that deoxyphomalone, NCGC00169066-01, and phloretin had inhibition potential against TNFα and NF-kB, and activation potential against SOD, due to several residues involved in the interaction of compounds-protein was the same as the interaction of inhibitor (SPD-304 and MG-132) and activator (gallic acid) control against the protein. The residues may have the same inhibition or activation mechanism as the control. However, S. polyanthum bioactive compounds may still have inhibition potential against KEAP1 through Ala548 residue that is also involved in the interaction of DMF-KEAP1. Conclusions: The bioactive compounds of S. polyanthum showed anti-inflammation and antioxidant potential, which may have a good effect in the treatment of PCOS, yet still need to be confirmed in vitro or in vivo research.